Deaf-Blindness through the Voices and Experiences of Parents and Educators. (20th May 2022) - Intini, Martina; Garrino, Lorenza; Conti, Alessio; Dimonte, Valerio; Borraccino, Alberto
Abstract: This qualitative study used the experiences of parents and educators to explore the developmental processes and behaviors of deafblind people of different ages and with different etiologies. It also explored which strategies of intervention and care employed by parents and educators best promote and stimulate the abilities and the autonomy of deafblind people. Eligible parents and educators were identified and recruited from the New York Parents Association for Deafblind and the Helen Keller National Center on Long Island using purposeful sampling. Seven mothers, one father, and two educators were interviewed using a narrative method. Data analysis was performed using Heideggerian hermeneutic phenomenology. The themes that emerged concern communication, expression of emotions, sense of self and external reality, autonomy, and the sphere of educational intervention. This research goes beyond existing knowledge on the syndromes/disabilities related to deafblindness, focusing instead on the combinations of varying degrees of hearing and sight deprivation.